Gender Bias in the Media: The Case of Iceland - Valgerður Jóhannsdóttir 1960-; Þorgerður Einarsdóttir 1957- (2015)
Fræðigreinar The news media are the most influential sources of information, ideas and opinion for most people around the world. Who appears in the news and who is left out, what is covered and what is not and how people and events are portrayed matter. Research has consistently shown that women are underrepresented in the news and that gender stereotypes are reinforced in and through the media. The 1995 Beijing Declaration and Platform for Action recognised the relationship between women and media as a major area of concern in achieving gender equality in contemporary societies. This article presents Nordic findings from the 2015 Global Media Monitoring Project (GMMP), which is the largest and longest-running study on gender in the world’s media. The findings show that women account for only 1 in 5 of the people interviewed or reported on by Icelandic news media and that women’s overall presence in the news has declined compared to the last GMMP study in 2010. The proportion of women as news subjects is also considerably lower than in other Nordic countries. We argue that the number of women who are journalists, managers in the media industry and decision makers in society has increased, but this shift has not automatically changed the representation of women in the news, either in numbers or in their portrayal. This discrepancy indicates that the relationship between gender and the news media is complicated and needs to be approached from different perspectives.